Análisis de la calidad de encolado en tableros compensados fenólicos de Eucalyptus spp. con diferentes condiciones de prensado en planta - Wegert, Flavia (2019)
In this work we studied the quality of gluing of phenolic compensated boards, using a grammage and pressing time lower than the production standard. Shear strength was compared in glued jointsaccording to IRAM 9562, of boards manufactured conventionally, and manufactured with new production parameters. No significant differences were found in the resistance of both boards. In addition, it was determined that boards manufactured with the new parameters have a higher percentage of acceptance of the relationship between shear strength and the percentage of wood failure.